Marine operators’ perception towards the new proposed environmental regulation : a case study of Svalbard, Norway - Carol Lopez 1975- (2023)
Svalbard, a Norwegian archipelago located in the Arctic Ocean, is experiencing rapid tourism growth. Simultaneously, the archipelago is undergoing dramatic environmental and climatic changes. These changes are noticeable through an increase in precipitation, a retreat in sea ice, changes in species distribution, and the melting of glaciers and ice caps. Some aspects of climate change contribute to the thriving tourism industry. For instance, the melting of sea ice may create new cruise tourism opportunities, and as a result, marine tour operators in the High Arctic will be able to expand the area and season of maritime activities. However, both climate change and the increase in tourism are a challenge for the Norwegian government concerning how to preserve Svalbard’s fragile environment while concurrently securing local economic development. To address this concern, my master’s thesis explored the perception and responses of marine tour operators in Svalbard towards these new environmental regulations proposed by the Norwegian Environmental Agency. I applied a qualitative case-study approach, conducted semi-structured interviews with marine tour operators in Svalbard, and included public hearing consultation statements. The result of my research demonstrated a clear negative perception and discontent with these newly proposed environmental regulations. The participants argued that in the future, it might damage the marine tourism industry. They concluded by stating they may have to shorten their season, do something different or leave Svalbard. Though my results addressed the perception of the new regulations and possible responses, future research should be carried out once environmental legislation comes into effect to deepen the understanding and impact on marine tour operators. Svalbarði, norskur eyjaklasi staðsettur í Norðurheimskauts hafinu, er að upplifa hraða aukningu á ferðaþjónustu. Um leið er eyjaklasinn að verða fyrir stórkostlegum umhverfisog loftslagsbreytingum. Þessar breytingar eru ...